A 13th-Century Shipyard at Alanya (Alaiyye), on the Mediterranean Coast of Turkey - Daggulu, Ibrahim Basak (WILEY-BLACKWELL PUBLISHING, INC, 2009)
Anatolian Seljuks, a territorially-powerful medieval government, held their fleet at bases on the Black Sea and Mediterranean coasts, and constructed permanent stone buildings to protect their navy. Although most of these buildings have disappeared, 13th-century defended shipyard buildings have survived at Alanya, on the Mediterranean coast of Turkey. These buildings are not only important architecturally, but can give clues to the types of warships used by the Anatolian Seljuk navy, of which little is known. The dimensions of the shipsheds help us to analyse the construction of these naval vessels. (c) 2009 The Author
Keywords: Anatolian; Seljuk; defensive buildings; medieval shipyard; medieval Seljuk galleys; Archaeology